Effect of information provision program by applying the health belief model on medication adherence in patients with glaucoma. - Rattanamanie, W.; Preechawong , S.; Tantisevi, V. (Chulalongkorn Medical Journal, 2023)
Background : The purpose of this research was to examine the effect of information provision program by applying the health belief model on medication adherence in patients with glaucoma. Research Design : Quasi-experimental research, pretest-posttest control group design. Setting : Eye Clinic, King Chulalongkorn Memorial Hospital. Methods : Fifty patients with glaucoma, were recruited from the Eye Clinic of King Chulalongkorn Memorial Hospital into this study. The participants were assigned into two groups, that were matched in term of gender, age, number of medications, years of having glaucoma: they were assigned equally into experimental and control group of 25. The control group received conventional nursing care while the experimental group participated in the information program by applying health belief model. The program consists of assessment, giving information, skills training on medication administration, and monitoring. The outcome was assessed at 4 weeks by the 15-item adherence questionnaire that had content validity index of .93 and internal consistency with alpha coefficients of .78. The data were analyzed using descriptive and t-test. Results : The results showed that after participating in the program, the mean score for medication adherence of the experimental group was significantly higher before the intervention (p <.05). In addition, the mean score medication adherence in the experimental group was significantly higher than that for the control (p<.05). Conclusion : The information provision program by applying the health belief model could be useful for nurses to promote medication adherence in patients with glaucoma.